Dry deposition of NO2 over China inferred from OMI columnar NO2 and atmospheric chemistry transport model. (November 2017) - Zhang, X.Y.; Lu, X.H.; Liu, L.; Chen, D.M.; Zhang, X.M.; Liu, X.J.; Zhang, Y.
Abstract: The NO2 dry deposition over China was estimated based on an inferential model, in which the surface NO2 concentrations and deposition velocities were derived from OMI columnar NO2 and the simulation results from atmospheric chemistry transport models. Nationally, the annual NO2 dry deposition fluxes ranged from 0.0005 to 8.54 kg N ha −1, with an average of 0.48 kg N ha −1 . The total NO2 dry deposition over China was 0.46 Tg N yr −1, mainly contributed by northern and southeast China. Due to contrary seasonal trends of the NO2 concentrations (high in cold months) and deposition velocities (high in warm months), the estimated NO2 dry depositions did not show strong seasonal pattern, instead showing relatively high values from August to October and low ones in February. The annual NO2 dry deposition has an increasing trend from 2007 to 2014, with the highest deposition level achieved in 2011. This research conducts a thorough validation between estimated NO2 dry depositions with ground measurements of NO2 concentrations and provides an objective spatial perspective and insight on the existing NO2 dry deposition maps in China. Highlights: NO2 dry deposition is estimated based on an inferential method. Surface NO2 is inferred from OMI NO2 column and MOZART-4. Deposition velocity for NO2 is simulated from a big-leaf model. NO2 dry deposition is 0.46 Tg N yr −1 over China, with no strong seasonal pattern. NO2 deposition increases from 2007 to 2014, with the highest in 2011.